LICENSING OF THE TOURIST ACTIVITY IN UKRAINE WITHIN THE CONTEXT OF THE INTERNATIONAL PRACTICE - Herasymenko, Viktor; Halasiuk, Svitlana (Journal of European Economy, 2017)
The place and the role of licensing of the tourist activity in the system of Governmental tourist management are considered. Modern approaches to the protection of the rights and legitimate interests of the participants of tourism market in different countries in the world and in Ukraine are analyzed. Particular arrangements, aimed to improve the tourism policy in Ukraine are suggested.